Pengembangan Video Pembelajaran Berbasis Pendekatan Saintifik Tema 6 Subtema 2 Kelas IV SDN Mojoagung 01 Kab Pati - Shely Permatasari; Arfilia Wijayanti; Eka Sari Setianingsih (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the validity, practicality and usefulness of the development of learning videos based on the Scientific approach for fourth grade elementary school. The type of research used by the researcher is research and development (Research and Development) which goes through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The learning media used were in the form of an existing learning video which was then developed into a scientific approach-based learning video for elementary school students. Based on the analysis, the percentage of media experts obtained is 96.5% with the